2018
DOI: 10.1167/iovs.18-24665
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Choroidal Stroma Reduces Accuracy of Automated Segmentation of Outer Choroidal Boundary in Swept Source Optical Coherence Tomography

Abstract: Automated outer choroidal boundary segmentation tends to identify the posterior limit of the choroidal vessel. Agreement between A-SFCT and M-SFCT is reduced by the presence of posterior stromal layer and lamina fusca. A-SFCT should be interpreted with RCJ and CSJ boundary grading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Several posterior boundaries of CT were proposed, and CT measurements can be substantially affected by the visibility of choroidscleral interface (CSI). [40][41][42][43][44] It was reported that automated outer choroidal boundary segmentation tends to identify the posterior limit of the choroidal vessel by SS-OCT. 40 Two investigators reviewed all the OCT scans, made correction when needed, and excluded images without clear choroid-scleral junction. However, the systematic errors could not be completely excluded due the wave length of the SS-OCT.…”
Section: Discussionmentioning
confidence: 99%
“…Several posterior boundaries of CT were proposed, and CT measurements can be substantially affected by the visibility of choroidscleral interface (CSI). [40][41][42][43][44] It was reported that automated outer choroidal boundary segmentation tends to identify the posterior limit of the choroidal vessel by SS-OCT. 40 Two investigators reviewed all the OCT scans, made correction when needed, and excluded images without clear choroid-scleral junction. However, the systematic errors could not be completely excluded due the wave length of the SS-OCT.…”
Section: Discussionmentioning
confidence: 99%
“…The findings presented here may be used to inform future work in the area of chorio-retinal boundary analysis in OCT images. Future studies should explore how these methods will perform in other OCT modalities, particularly swept-source OCT that has demonstrated a superior performance to visualize the deeper choroidal layer 85 compared to spectral domain OCT used in this study. It is worth noting that the images used in the current study are from young healthy participants, and therefore further work is required to examine these segmentation methods in cases of ocular pathology and in older populations.…”
Section: Discussionmentioning
confidence: 99%
“…3D image analysis and choroidal 2D maps using SS-OCT images are potentially useful to explore the unknown pathogenesis of the choroid. To accomplish this purpose, the choroidal segmentation has several problems that cannot be easily overcome; low contrast of the C-S boundary, a deficit of the inner surface of the sclera, namely scleral canals for vessels or nerves, and the presence of a posterior stromal layer and lamina fusca 27 .…”
Section: Discussionmentioning
confidence: 99%